O propovijedima iz Postile (1568) Antuna Dalmatina i Stipana Konzula - Šundalić, Zlata (Slavia Centralis, 2020)
O pridigah iz Postile (1568) Antuna Dalmatina in Stipana KonzulaThis paper analyses sermons from Antun Dalmatin’s and Stipan Konzul’s Latin script edition of Postila (Regensburg 1568). Postila was intended for Croatian emigrants, especially those in Željezno and its surroundings. Therefore, its translators are considered to be the creators of Burgenland Croatian literature. The introduction lists important determinants of Croatian protestant literature, while the central part of this paper analyses Advent sermons. To be more exact, eight Sunday sermons are examined, because one chapter from the gospels for every Sunday of Advent is interpreted through two sermons (omilije – homilies, for example: Parva omilija od prave vire ili časti Božje, Druga omilija parve nedile od prišašća). They were shaped according to a common model: each starts by addressing the gathered worshipers, which was followed by defining the topic and its explanation with a conclusion which was always optimistic in emphasizing that the Son of God is coming for our salvation and not for our damnation. To conclude this paper we examine which determinants of Croatian protestant literature are confirmed by the analyzed Advent sermons.
Keywords: Protestantism; Postila; sermon; content; structure; style